PENERAPAN ASAS PRADUGA TAK BERSALAH DALAM PEMBERITAAN PERS YANG TIDAK SEIMBANG - Iwan, Iwan (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACTThat there is still a tendency to display the news of sensations in excess or dramatization disproportionately by the press. So to change the public appreciation of the news depends on the intention of the press itself, this is where the role of the press as agents of change and social control. That against them (news sources) who have the power, either state authority or economic power, they will try to avoid the news that they claim to be harmed. As for them (news sources) who do not have power and power like many people, of course the press must protect because one of the main functions of the press is to protect the people in accordance with the slogan "journalists are protector of democracy". Legal conditions that put the subordinate press with the government to make journalists are not free in expression, interpretation and others. Many limitations are not clear either from the government or from the managers of the press itself that ultimately the sensitivity of journalists in the face of social reality becomes dull. As a result that happens journalist (pers) only serves as public relations (mouthpiece) government.Keywords : Press Coverage, Unclaimed Guilt Principle